LOBULAR CAPILLARY HAEMANGIOMA OF THE NASAL CAVITY IN PREGNANCY: A CLINICAL CASE STUDY - Lutfullaev G.U.; Neymatov U.S.; Khamraev F.H. (Scholar Express Journals, 2024)
This article presents a case of nasal haemangioma, a patient in the 32nd week of pregnancy, whose main complaints were the following symptoms: absence of nasal breathing, anosmia and recurrent nosebleeds, marked nasal dyspnoea. Treatment consisted of complete removal by endonasal resection. The patient underwent endonasal resection. Vascular tumours of the nasal cavity can occur in men and women of any age. They can occur in men and women of any age group. This article presents a case of nasal haemangioma diagnosed in a patient at 32 weeks of gestation.
Keywords: capillary haemangioma; nasal septum; nasal bleeding